A taxonomic synopsis of South American Cyanogomphini Carle with description of Cyanogomphus angelomachadoi sp. nov. from the Cerrado of Brazil (Odonata: Gomphidae) - Pinto, Ângelo Parise; Almeida, Marcus Vinícius Oliveira De (Zootaxa, 2016)
A synopsis of Cyanogomphini Carle, 1986 (sensu Belle 1996), including all species currently under the genera Cyanogomphus Selys, 1873, and Tibiagomphus Belle, 1992, is provided. Cyanogomphus angelomachadoi sp. nov. (Holotype ♂ deposited in DZRJ: Brazil, Minas Gerais State, Jaboticatubas municipality, Parque Nacional da Serra do Cipó, collecting site “Córrego das Pedras” 19°22’17”S, 43°36’03”W, 766 m a.s.l., 12.XII.2011, A.P.M. Santos & D.M. Takiya leg.) is described and illustrated based on four males and two females from Minas Gerais and São Paulo States, southeastern Brazil. The new species is most similar to C. waltheri Selys, 1873, from which it can be distinguished by its smaller size; larger pale areas on mesepisternum; pale dorsal surface of metathoracic tibia; larger distal concavity on epiproct, with laterodistal projection, in lateral view forefinger-shaped; and occurrence in Cerrado province. Five species are recognized in Cyanogomphini, and for each one a synonymy, diagnoses, identification key and maps of distribution are presented. The status of sibling taxa Tibiagomphus uncatus (Fraser, 1947) and T. noval (Rodrigues Capítulo, 1985), as well as the Agriogomphus-complex of genera are also discussed.